Evidence-Based Endocrinology - Montori, Victor M. (Contemporary Endocrinology, 2006)
Evidence-based medicine (EBM) stresses the use of evidence from clinical research as the basis for medical decision making, rather than simple reliance on unsystematic clinical experience and pathophysiological rationales. EBM has changed many aspects of medical practice for the better, but its incorporation into endocrine practice has been minimal. In Evidence-Based Endocrinology, internationally recognized experts, pioneers, and opinion makers in EBM provocatively recast endocrine policy and practice in the light of its philosophy and principles. The authors explain the past, present, and future of EBM; consider its practical implications for endocrinology; demonstrate what the "evidence base" is in EBM; and present illustrative case studies by practicing evidence-based clinicians. Highlights include essays on why cost-effective analyses are problematic, the contrast between clinical investigations and large randomized trials, the role of Cochrane reviews and meta-analyses, and the curriculum requirements for training evidence-based endocrinologists. Authoritative and cutting-edge, Evidence-Based Endocrinology not only spells out the high value of EBM, but also its limitations, challenging endocrinologists to embrace its principles in the best interests of their patient practice.